Intake, digestibility and nitrogen utilization by sheep fed with provenances of Calliandra calothyrsus Meissner with different tannin structure - Lascano Aguilar, Carlos Eduardo; Ávila Vargas, P.; Stewart, J (2003)
A trial with sheep (housed in metabolic cages, and fitted with ruminal and duodenal cannulas) fed sun-dried forage of two Calliandra calothyrsus provenances (San Ramon —CIAT 22310 and Patulul CIAT— 22316) harvested in sites with contrasting soil fertility was carried out to further define the biological significance of the different chemical structure in the tannin of Calliandra provenances. Six African-type sheep were assigned to one of four treatments (T1: San Ramón grown in Quilichao with infertile soils, T2: Patulul grown in Quilichao with infertile soils, T3: San Ramón grown in Palmira with fertile soils, and T4: Patulul grown in Palmira with fertile soils) arranged in an Unbalanced Simple Crossover Design. Results showed that extractable tannins in Patulul comprised mainly procyanidin subunits, whereas the tannin fraction in San Ramón was composed largely of prodelphinidin subunits. The DM intake and digestibility of Calliandra were greater (P<0.05) with San Ramón than with Patulul. Intake was also greater (P<0.05) with provenances harvested in the site with fertile soil than in the site with acid soils. Absolute and relative values of ruminal escape dietary N in sheep were greater (P<0.05) with San Ramón than with Patulul, which is consistent with laboratory results on tannin astringency. Thus for the first time we have evidence suggesting that the chemical structure of condensed tannins in tropical legumes can have an effect on N utilization by ruminants. The fact that in vivo results on ruminal escape N were in close agreement with results on astringency of extractable condensed tannins from Calliandra provenances validates the use of laboratory astringency tests for screening tropical legumes with tannins for quality traits.